2003
DOI: 10.1161/01.cir.0000054613.57105.06
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Therapy After Acute Myocardial Infarction

Abstract: Background-Infection with Chlamydia pneumoniae is suspected to contribute to the pathogenesis of human atherosclerosis. We investigated whether treatment with the macrolide antibiotic roxithromycin would reduce mortality or morbidity in patients with an acute myocardial infarction. Methods and Results-Eight hundred seventy-two patients with an acute myocardial infarction (AMI) were randomly assigned to receive double-blind treatment with either 300 mg roxithromycin or placebo daily for 6 weeks. Primary end poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(24 citation statements)
references
References 26 publications
0
21
0
3
Order By: Relevance
“…Trial populations were slightly variable. Six trials were conducted among patients with stable coronary artery disease (10,(13)(14)(15)(16)(17) and six trials involved patients with acute coronary syndromes (18)(19)(20)(21)(22)(23). The remaining trial was conducted among patients scheduled to undergo coronary artery bypass graft surgery (24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trial populations were slightly variable. Six trials were conducted among patients with stable coronary artery disease (10,(13)(14)(15)(16)(17) and six trials involved patients with acute coronary syndromes (18)(19)(20)(21)(22)(23). The remaining trial was conducted among patients scheduled to undergo coronary artery bypass graft surgery (24).…”
Section: Resultsmentioning
confidence: 99%
“…Three trials (10,13,14) included anti-Chlamydia immunoglobulin (Ig)G titres as part of their inclusion criteria. Trials examined the use of one of four different antibiotics: azithromycin (seven trials) (10,(13)(14)(15)(19)(20)(21), roxithromycin (two trials) (17,22), clarithromycin (three trials) (16,23,24) and gatifloxacin (one trial) (18).…”
Section: Resultsmentioning
confidence: 99%
“…With the publication in this issue of Circulation of a clinical trial of antibiotic treatment of patients after acute myocardial infarctions, 1 there are now 12 published clinical trials of antibiotic treatment for secondary prevention of atherosclerotic cardiovascular disease. [1][2][3][4][5][6][7][8][9][10][11][12] Two additional trials, not yet published, were presented at the 2002 Annual Scientific Sessions of the American College of Cardiology.…”
Section: See P 1253mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Two additional trials, not yet published, were presented at the 2002 Annual Scientific Sessions of the American College of Cardiology. They are Weekly Intervention with Zithromax for Atherosclerosis and its Related Disorders (WIZARD) and AZithromycin in Acute Coronary Syndromes (AZACS).…”
Section: See P 1253mentioning
confidence: 99%
“…The ANTIBIO (Antibiotic Therapy in Acute Myocardial Infarction) study [104] found that a 6-week course of roxithromycin showed no benefits in 872 patients with acute myocardial infarction after a 1-year follow-up.…”
Section: Trials With Antibioticsmentioning
confidence: 99%